Viral-Mediated AURKB Cleavage Promotes Cell Segregation and Tumorigenesis - Zhu, Qing; Ding, Ling; Zi, Zhenguo; Gao, Shujun; Wang, Chong; Wang, Yuyan; Zhu, Caixia; Yuan, Zhenghong; Wei, Fang; Cai, Qiliang (Cell reports (Cambridge), 2019)
Aurora kinase B (AURKB), a central regulator of chromosome segregation and cytokinesis, is aberrantly expressed in various cancer cells. However, the relationship of AURKB and oncogenic viruses in cancer progression remains unclear. Here, we reveal that N-cleaved isoforms of AURKB exist in several oncovirus-associated tumor cells and patient cancer tissues, including Kaposi’s sarcoma-associated herpesvirus (KSHV), Epstein-Barr virus (EBV), and human papillomavirus virus (HPV). Mechanistically, in KSHV-infected tumor cells, the latent viral antigen LANA cleaves AURKB at Asp76 in a serine protease-dependent manner. The N′-AURKB relocalizes to the spindle pole and promotes the metaphase-to-telophase transition in mitotic cells. Introduction of N′-AURKB but not C′-AURKB promotes colony formation and malignant growth of tumor cells in vitro and in vivo using a murine xenograft model. Altogether, our findings uncover a proteolytic cleavage mechanism by which oncoviruses induce cancer cell segregation and tumorigenesis. [Display omitted] •Cleaved AURKB exists in many oncovirus-related cancer cells and patient cancer tissue•Oncovirus-mediated AURKB cleavage occurs at Asp76 and relies on a serine protease•The N′-AURKB promotes the metaphase-to-telophase transition in mitotic cells•The N′-AURKB promotes tumor growth and malignancy in vitro and in vivo Zhu et al. find that proteolytic cleavage of AURKB occurs in several oncovirus-associated cancer cells. Specifically, the oncovirus antigen LANA cleaves AURKB to promote the metaphase-to-telophase transition, thereby inducing host cell segregation and tumorigenesis.